Dari Teori ke Praktik: Strategi Responsivitas Hukum terhadap Tantangan Ekonomi dan Sosial - Bok Rok Su (CV Rewang Rencang, 2024)
This study aims to examine the responsiveness of Indonesia’s legal system to contemporary social and economic dynamics. Employing a qualitative-descriptive approach with an exploratory case study design, the research explores how legal policies—such as the Job Creation Law and the Omnibus Law—are implemented and how effectively they address the needs of society, particularly marginalized groups. Findings reveal a significant gap between the theory of responsive law—which emphasizes adaptability, public participation, and substantive justice—and legislative practices that remain top-down, lacking transparency, and heavily influenced by political and economic interests. Bureaucratic rigidity, low legal literacy, and social inequality further hinder the implementation of genuinely responsive laws. This research highlights the urgency of institutional reform, capacity-building for legal actors, and active civil society engagement in policymaking. Thus, the law can transform into a tool for social and economic empowerment, rather than merely an instrument of control. The findings are expected to contribute both theoretically and practically to the development of a more adaptive, inclusive, and equitable legal system in Indonesia.